Conservation and production potential of an agro-forestry system integrating grey gum (Eucalyptus tereticornis), white popinac (Leucaena latisiliqua) and turmeric (Curcuma longa) - Grewal, S S; Singh, Kehar; Juneja, M L (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during 1986-92 to study the performance of an agro-forestry system integrating grey gum (Eucalyptus tereticornis Smith) for pole wood on border rows of 40 m x 40 m plot, ’K 8’ white popinac [Leucaena latisiliqua (L.) Gillis; synL. leucocephala (Lam.) de Wil for organic mulch and manure in paired rows along the plots of shade-loving turmeric (Curcuma tonga L.; syn C. domestica Val). The soil was typical sandy loam (Udic Ustocrept) of foot-hill in north India. The agro-forestry system recorded run-off 2.7%, soil loss 0.54 tonnes/ha/year, N loss 2.1 kg/ha/year and K loss 0.7 kg/ha/year with mean monsoon-season rainfall of 899 mm compared with run-off 25 .4%, soil loss 3.21 tonnes/ha/year, N loss 12.5 kg/ha/year and K loss 4.3 kg/ha/year from the field crops raised under comparable conditions. The tuber yield of turmeric varied from 0.56 tonne/ha in low-rainfall to 4.73 tonnes/ha in high-rainfall years, with the mean annual yield 2.34 tonnes/ha and net return Rs 3 184/ha. White popinac provided 2 901 kg over-dry foliage in 4 years for mulching and its subsequent incorporation, and added 91.9, 4.2 and 44.3 kg/ha or N, P and K respectively into the soil. Grey gum poles (380) harvested after 6.5 years gave income of Rs 18 380. The agro-forestry system generated cash return of Rs 5 642/ha/year compared with Rs 2 997 from raifed crops and thus proved economically more viable than the normal system of growing field crops.